Charlie's Angels - McG; Murray, Bill, 1950-; Drew Barrymore; Kelly Lynch; Lucy Liu; Sam Rockwell; Tim Curry; Cameron Diaz (USA Germany Columbia Pictures Corporation, 2000)
Based on the popular 70's TV show, three cute chicks work for the mysterious ""Charlie"". They are the female 'James Bonds'' of our time. They get to blow stuff up, kick the cr*p out of people, and wear really tight clothing, all whilst trying to retrieve stolen software and balance in high heels.
Three women, detectives with a mysterious boss, retrieve stolen voice-ID software, using martial arts, tech skills, and sex appeal.
Ivan Goff
Language: English
Subtitles: English, Nederlands, Arabic, Bulgarian, Czech, Dansk, Suomi, Hindi, Magyar, Islenka, Norsk, Polish, Svenska, Turkish, Nederlands
Keywords: Adventure; Comedy; Action